PENGARUH CITRA MEREK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE - Tasya Salsabila Adel Putri chaniago (Universitas Linggabuana PGRI Sukabumi, 2021)
Brand image is the representation and overall perception of the brand and formed from past information and experiences on a lifestyle brand is one's lifestyle in a world expressed in its activities, interests, and opinions. When the brand image and lifestyle have a positive influence, it becomes a separate consideration for consumers and can influence consumer purchasing decisions. The purpose of the study this is to know the influence of Brand Image and Lifestyle to the decision of purchasing IPhone to MBS FEBI UIN RIL class of 2019 students. The method used in this research is quantitative method. This research took 30 samples. Sampling technique is purposive sampling technique. Data collection is done by questionnaire technique. Data analysis method used is multiple linear regression analysis, classical assumption test, F test, t test, coefficient of determination.